2015
DOI: 10.1186/s40575-015-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of whole-genome sequencing of four Chinese crested dogs for variant detection using the ion proton system

Abstract: BackgroundNext generation sequencing (NGS) has traditionally been performed by large genome centers, but in recent years, the costs for whole-genome sequencing (WGS) have decreased substantially. With the introduction of smaller and less expensive “desktop” systems, NGS is now moving into the general laboratory. To evaluate the Ion Proton system for WGS we sequenced four Chinese Crested dogs and analyzed the data quality in terms of genome and exome coverage, the number of detected single nucleotide variants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…Noteworthy, it was higher than Sayyab et al who used Ion Proton technology and reported an average sequencing depth of 9.2X and that 96% of the genome was covered at least 1X [22]. Viluma et al, who carried out another Ion Proton study, determined that 80% of the genome was covered at least 4X [60]; this is vastly different from our data, which covered 99.1% of the genome at 5X or greater. Similar to the two Ion Proton studies, our group also sought to determine the coverage of the canine exome through our WGS efforts.…”
Section: Discussioncontrasting
confidence: 99%
“…Noteworthy, it was higher than Sayyab et al who used Ion Proton technology and reported an average sequencing depth of 9.2X and that 96% of the genome was covered at least 1X [22]. Viluma et al, who carried out another Ion Proton study, determined that 80% of the genome was covered at least 4X [60]; this is vastly different from our data, which covered 99.1% of the genome at 5X or greater. Similar to the two Ion Proton studies, our group also sought to determine the coverage of the canine exome through our WGS efforts.…”
Section: Discussioncontrasting
confidence: 99%
“…Qualities of these SNPs were measured in terms of transition-to-transversion ratio (Ti/Tv). They were 2.03, 2.05, and 2.04 for LT, ST, and NT populations, respectively, similar to those reported in previous studies 17 . These SNPs were classified into synonymous, non-synonymous, splice site, intron, untranslated regions, and intergenic SNPs (Table 1 ).…”
Section: Resultssupporting
confidence: 90%
“…In addition, the WGS data will remain useful even when the annotation of the canine reference genome is further improved. The Ion Proton System (Thermo Fisher Scientific/Life Technologies) has previously been evaluated for WGS of dogs ( Viluma et al 2015 ), and in the present study we applied the technology to perform WGS of a family trio as a straightforward approach to discover genetic variants associated with an autosomal recessive disease termed Hereditary Footpad Hyperkeratosis (HFH) segregating in the Kromfohrländer breed. This allowed the identification of a missense variant in FAM83G (c155G > C, p.R52P) associated with HFH.…”
mentioning
confidence: 99%